2018
DOI: 10.3889/oamjms.2018.338
|View full text |Cite
|
Sign up to set email alerts
|

Overview of MDM2 and B-RAF Expression in Gastric Lesions

Abstract: BACKGROUND:Globally, gastric cancer (GC) it is the fourth most common cancer and the third cause of cancer-related deaths. Overexpression of MDM2 and B-RAF appeared to be increased in malignancy and associated with poor prognosis in several human tumours, but their role in gastric cancer remains controversial.AIM:We had investigated the immunohistochemical expression of MDM2 and B-RAF in 136 gastric lesions with/without H. pylori association.MATERIAL AND METHODS:Studied specimens include chronic gastritis (32)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…MAPK signaling pathway is reported to be involved in GC invasion and metastasis 35 BRAF, a member of RAF/MEK/ERK signaling pathway, is usually activated by a complex series of events 36 . BRAF is the most frequently mutated serine/threonine kinase in human cancers, 37 it is mutated in approximately 7% of all cancers, including GC, 38,39 and its overexpression is reported in GC 40 . RAF family members can phosphorylate and activate MEK and ERK with different biochemical potencies 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…MAPK signaling pathway is reported to be involved in GC invasion and metastasis 35 BRAF, a member of RAF/MEK/ERK signaling pathway, is usually activated by a complex series of events 36 . BRAF is the most frequently mutated serine/threonine kinase in human cancers, 37 it is mutated in approximately 7% of all cancers, including GC, 38,39 and its overexpression is reported in GC 40 . RAF family members can phosphorylate and activate MEK and ERK with different biochemical potencies 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Being a P53-specific E3 ubiquitin ligase, MDM2 is a principal factor in P53 destruction (28). MDM2 has proved to play an essential role in cancer progression by inducing cell proliferation, invasion, and therapeutic resistance and inhibiting the apoptotic process, serving as a useful predictive marker for poor prognosis in various human cancers such as GC, breast cancer, hepatocellular carcinoma, and lung cancer (11,(29)(30)(31). MDM2 expression parameters are closely correlated with H. pylori infection and higher stages GC (29).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that MDM2 amplification has been detected in several types of cancer, including GC (10,19). In GC, MDM2 has been shown to be amplified (12) and overexpressed in GC tissues (36,37), and this has also been associated with a higher grade of tumor differentiation, deeper invasion and nodal and distant metastasis (37).…”
Section: Discussionmentioning
confidence: 99%